Diagnostic value of biomarkers in multiple sclerosis - Zafranskaya, Marina M. (Journal of the Belarusian State University. Ecology, 2019)
Multiple sclerosis (MS) is a classic neuroinflammatory disease involving the aberrant balance of T-, B- and myeloid cells (including microglia), which are potential targets for the manifestation of biomarkers. Presently, based on prospective randomized clinical trials, genetic and cell biomarkers allowing adequately disclosing / assessing all aspects of the immune system damage due to MS and to personalize the selective immunotherapy taking into account the inflammatory status, cellular and humoral sensitization of a patient have been validated. However, additional studies are required to implement the obtained results into clinical practice. Biomarkers are objective indicators of physiological and pathological processes; in clinical settings, they can be used as a diagnostic, prognostic and therapeutic tool. In MS, the identification of definite biomarkers may be of exceptional interest for developing specific prognostic methods to predict therapeutic efficacy and personalize the treatment protocol.